High Hole Mobility Polycrystalline GaSb Thin Films - Anya Curran (MDPI AG, 2021)
In this paper, we report on the structural and electronic properties of polycrystalline gallium antimonide (poly-GaSb) films (50–250 nm) deposited on p+ Si/SiO2 by metalorganic vapour phase epitaxy at 475 °C. GaSb films grown on semi-insulating GaAs substrates are included as comparative samples. In all cases, the unintentionally doped GaSb is p-type, with a hole concentration in the range of 2 × 1016 to 2 × 1017 cm−3. Exceptional hole mobilities are measured for polycrystalline GaSb on SiO2 in the range of 9–66 cm2/Vs, exceeding the reported values for many other semiconductors grown at low temperatures. A mobility of 9.1 cm2/Vs is recorded for an amorphous GaSb layer in a poly-GaAs/amorphous GaSb heterostructure. Mechanisms limiting the mobility in the GaSb thin films are investigated. It is found that for the GaSb grown directly on GaAs, the mobility is phonon-limited, while the GaSb deposited directly on SiO2 has a Coulomb scattering limited mobility, and the poly-GaAs/amorphous GaSb heterostructure on SiO2 displays a mobility which is consistent with variable-range-hopping. GaSb films grown at low temperatures demonstrate a far greater potential for implementation in p-channel devices than for implementation in ICs.